Temperature dependent structural variations of OH−(H2O)n, n = 4–7: effects on vibrational and photoelectron spectra1. Issue 29 (7th August 2015) - Lin, Ren-Jie; Nguyen, Quoc Chinh; Ong, Yew-Soon; Takahashi, Kaito; Kuo, Jer-Lai
<x xml:space="preserve">Abstract</x> In this work, we identified a large number of structurally distinct isomers of midsized deprotonated water clusters using first-principles methods.